2002
DOI: 10.2134/agronj2002.0365
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Recycling by Nonleguminous Winter Cover Crops to Reduce Leaching in Potato Rotations

Abstract: if (i) sufficient heat units are available to promote cover crop growth, root exploration, and N uptake during fall and winter; and (ii) mineralization rates of the green-Overwinter N leaching increases the potential for NO 3 contamination of ground water under irrigated desert soils. Our objectives were manured residues in the spring coincide with the timing to (i) identify winter cover crops for recovering N and (ii) determine of cash crop N demand. Effective fall-sown cover crops the N availability followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
74
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 1 publication
(1 reference statement)
4
74
1
Order By: Relevance
“…At Ridgetown, OSR and OSR&Rye had higher biomass and plant N content compared with that observed by Vyn et al (2000) and Weinert et al (2002). The high plant N content in OSR and OSR&Rye treatments at Ridgetown was likely due to the fact that plants reached physiological maturity and set viable seed.…”
Section: O'reilly Et Al * N and Corn Profits With Fall Cover Crops 357mentioning
confidence: 70%
See 4 more Smart Citations
“…At Ridgetown, OSR and OSR&Rye had higher biomass and plant N content compared with that observed by Vyn et al (2000) and Weinert et al (2002). The high plant N content in OSR and OSR&Rye treatments at Ridgetown was likely due to the fact that plants reached physiological maturity and set viable seed.…”
Section: O'reilly Et Al * N and Corn Profits With Fall Cover Crops 357mentioning
confidence: 70%
“…Soil mineral N was likely higher in OSR&Rye than oat and rye treatment due to rapid decomposition of OSR leaf and root tissues. After a killing frost, Weinert et al (2002) also found that rye had lower soil mineral N levels than a no-cover and a Brassica cover crop.…”
Section: O'reilly Et Al * N and Corn Profits With Fall Cover Crops 357mentioning
confidence: 88%
See 3 more Smart Citations